New strategies for reputation management : gaining control of issues, crises and corporate social responsibility. - Griffin, Andrew, ....- (London : Kogan Page, 2008)
Introduction; Reputation management today; The corporation under fire; Regaining the reputation initiative; Crisis management - leadership in a tried and tested system; Issues management - shaping the agenda; Social responsibility - your initiatives on your initiative; Turning the corner - the corporation on the couch
Keywords: Bedrijfsimago; Crisiscommunicatie